2014
DOI: 10.1007/s12195-014-0342-y
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Deformability Constitutes a Rate-Limiting Step During Cell Migration in 3-D Environments

Abstract: Cell motility plays a critical role in many physiological and pathological settings, ranging from wound healing to cancer metastasis. While cell migration on 2-dimensional (2-D) substrates has been studied for decades, the physical challenges cells face when moving in 3-D environments are only now emerging. In particular, the cell nucleus, which occupies a large fraction of the cell volume and is normally substantially stiffer than the surrounding cytoplasm, may impose a major obstacle when cells encounter nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
343
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(368 citation statements)
references
References 45 publications
22
343
2
1
Order By: Relevance
“…We also quantitatively investigated the influence of transmigration on cell nuclei, including nuclear shapes, chromatin deformations, and NE deformations. Our results predict nuclear shape profiles that closely agree with both our experimental observations and previously published data (8,9,13,25). Furthermore, investigating the nuclear profiles and the distribution of strain within the nucleus, we conclude that the primary driving forces (particularly for transmigration through small gaps) are those that pull the nucleus from the front.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We also quantitatively investigated the influence of transmigration on cell nuclei, including nuclear shapes, chromatin deformations, and NE deformations. Our results predict nuclear shape profiles that closely agree with both our experimental observations and previously published data (8,9,13,25). Furthermore, investigating the nuclear profiles and the distribution of strain within the nucleus, we conclude that the primary driving forces (particularly for transmigration through small gaps) are those that pull the nucleus from the front.…”
Section: Discussionsupporting
confidence: 90%
“…4 a). This hourglass shape has been observed in various cell migration experiments (8,13,25,39). Interestingly, our model predicts that E 1 and E 2 are mostly tensile and compressive, respectively, consistent with the experimental patterns of strain maps derived based on the triangulation between the individual, naturally present dense chromatin foci (Fig.…”
Section: Pulling Forces As the Primary Mechanism Of Transmigrationsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar studies of others likewise showed enhanced migration in vitro 3,19 . The nuclear lamina has likely evolved to protect the genome and enhance cell viability.…”
Section: Introductionsupporting
confidence: 85%